2022
DOI: 10.3390/catal12020189
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Coupling of Methane over Pt/Al2O3 at High Temperature: Multiscale Modeling of the Catalytic Monolith

Abstract: At high temperatures, the oxidative coupling of methane (OCM) is an attractive approach for catalytic conversion of methane into value-added chemicals. Experiments with a Pt/Al2O3-coated catalytic honeycomb monolith were conducted with varying CH4/O2 ratios, N2 dilution at atmospheric pressure, and very short contact times. The reactor was modeled by a multiscale approach using a parabolic two-dimensional flow field description in the monolithic channels coupled with a heat balance of the monolithic structure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
3
7
0
Order By: Relevance
“…In summary, REO addition to a Pt/Al 2 O 3 OCM catalyst was found to be beneficial, as the C 2 selectivity was at least equal to the reference sample 100Al at high dilutions and promoted at lower dilutions. As for both Pt-OCM [30] and REO-driven OCM [28] a dependency on gas phase reactions and thus methyl radical formation was reported previously, one can deduce that for our catalyst systems these effects occur simultaneously, hereby improving C 2 formation. Zhou et al [28] found Sm 2 O 3 as the most effective compound for CH 3 • generation, which outperformed other REOs by far; however, the same study also revealed La 2 O 3 as the dopant yielding the highest C 2 selectivity, followed by Sm 2 O 3 .…”
Section: Variation Of the Reo Dopantsupporting
confidence: 85%
See 4 more Smart Citations
“…In summary, REO addition to a Pt/Al 2 O 3 OCM catalyst was found to be beneficial, as the C 2 selectivity was at least equal to the reference sample 100Al at high dilutions and promoted at lower dilutions. As for both Pt-OCM [30] and REO-driven OCM [28] a dependency on gas phase reactions and thus methyl radical formation was reported previously, one can deduce that for our catalyst systems these effects occur simultaneously, hereby improving C 2 formation. Zhou et al [28] found Sm 2 O 3 as the most effective compound for CH 3 • generation, which outperformed other REOs by far; however, the same study also revealed La 2 O 3 as the dopant yielding the highest C 2 selectivity, followed by Sm 2 O 3 .…”
Section: Variation Of the Reo Dopantsupporting
confidence: 85%
“…2C). Since sufficiently high temperatures were reported as prerequisite for methyl radical formation, subsequent gas phase recombination to form C 2 H 6 , and subsequent dehydrogenation [27,[29][30][31], this more pronounced heat evolution is, in addition to methyl radical production from heterogeneous reaction pathways, an important factor that enables the higher C 2 selectivities observed over the REO-doped catalyst samples (Fig. 1A).…”
Section: Variation Of the Reo Dopantmentioning
confidence: 92%
See 3 more Smart Citations